A case of Mycoplasma pneumoniae‐induced rash and mucositis with recent influenza vaccination - Vani Agarwal; Georgie Gamble; Alexander Amphlett; Neil P. Patel (Wiley, 2024)
Abstract A 33‐year‐old female presented with coryzal symptoms, facial swelling, severe haemorrhagic stomatitis, blistering oral mucositis, conjunctival injection and a sparse targetoid rash on the back and face, requiring admission to hospital. She had received the seasonal influenza vaccination 3 days prior to feeling unwell. Differential diagnosis included erythema multiforme major (EMM) secondary to the influenza vaccine or Mycoplasma pneumoniae‐induced rash and mucositis (MIRM). Oropharyngeal swabs were negative on PCR for cutaneous viruses and Mycoplasma pneumoniae (MP). A skin biopsy from a targetoid lesion on the body showed full thickness epidermal necrosis with epidermal-dermal clefting, numerous civatte bodies and a moderate perivascular infiltrate of lymphocytes and plasma cells in the papillary dermis. She was successfully treated with oral prednisolone and azithromycin. Following discharge from hospital, the paired serological testing for MP returned positive, confirming a diagnosis of MIRM. Our case highlights the difficulties in detecting MP as two diagnostic methods yielded different results, and so we advocate performing both MP PCR and serology to maximise the yield and speed of diagnosis. Secondly, our case highlights the clinical challenge in differentiating MIRM from EMM or Stevens-Johnson syndrome, particularly if there is a potential drug trigger (in our case the influenza vaccine), as all these conditions can feature a severe mucositis with often indistinguishable histological findings. Correct diagnosis of MIRM is important for appropriate and timely administration of anti‐MP antibiotic therapy to facilitate recovery and minimise complications.